Local Government in Greece at the Crossroads: Between Governability and Accountability - Karvounis, Antonios (HAPSc Policy Briefs Series, 2021)
This policy brief is based on the assumption that the recovery of Greece, after more than a decade of crisis, should include local government, the institution, which is closer to local people than central government, and, consequently, ought to be more accountable. One of the most important problem identified here is the democratic deficit of the first level of local governance system. Despite its strong political and social clout, local government in Greece remains an institution with limited capabilities, as the Greek State has been and remains one of the most centralized states in Europe. In fact, after the 2019 general election, just before and during the recent pandemic crisis, the legislative initiatives of the government, despite the international trends of decentralisation towards more participatory and accountable local institutions, turned to the traditional and favourite “mayor-centered” system of local governance for the sake of the “governability”. As a result, the re-concentration politics of local government loom large for the post-coronavirus era.